THE FIRST EXPERIENCE OF MULTICOMPONENT PLASTIC MK WITH STRENGTHENING OF THE ANNULUS WITH VASCULAR PROSTHESIS - E. A. Rizayev; F. F. Turaev (Евразийский Кардиологический Журнал)
The rapid progression of the disease and the low effectiveness of conservative treatment determine the need for early diagnosis and surgical correction. Surgical treatment of the pathology of the mitral valve (MV) is a constant subject of clinical and scientific interest, despite the progress made in surgery of the MV. Until recently, in the overwhelming majority of cases, patients underwent mitral valve replacement (MVR), which forced only patients with a fairly pronounced clinic of heart failure who had a prosthesis implantation to operate on. However, valve prosthesis, on the one hand, solves the problem of mitral defect recurrence, on the other hand, it determines the risk of left ventricular (LV) remodeling with impairment of its function. Performing a valve-preserving operation is considered more preferable than prosthetics for a number of objective reasons: a favorable p/o course, the absence of lifelong administration of anticoagulants, no risk of thromboembolic complications. The most common methods of mitral valve repair in case of its insufficiency are methods of multicomponent plastics using various artificial support rings and half-rings (rigid, semirigid, flexible). The aim of the study was to present the first experience of multicomponent plastic MV with strengthening of the annulus with a vascular prosthesis. In the department of faculty RSCPMCS nam.af.akad.Vahidova from 2010 to 2019 y. 94 multicomponent plastics on the MC were performed, while FR annuloplasty was performed according to the original method. Considering the rheumatic etiology of the valve leaflets, all patients were also dissected and mobilized supporting chords, resected secondary chords of the BD MV. After multicomponent reconstructions, a hydraulic test was carried out, during which the regurgitation on the MV did not exceed the I st. To prevent the postoperative fibrous ring from dilating, in order to strengthen the posterior semicircle of BD MV, all patients underwent implantation of a strip from a vascular prosthesis on separate U-shaped sutures Etibond 2/0. The length of the strip was selected taking into account the developed nomograms and coefficients for the calculation of individual standard values of the diameter of the MV. Repeated hydraulic test showed almost disappearance of residual regurgitation, which was also determined on intraoperative TE-EchoCG. The average area of the mitral orifice was 2.8 ± 0,2 sq. Cm. The average gradient on the MV was 4,3 ± 0,5 mm Hg. The average aortic clamping time was 88.5 ± 10,2 min. The average term of the p / o MV was 8 ± 2 hours, the average stay in the ICU was a day, all patients were discharged for 7-8 days with a sinus rhythm, with a recommendation to take indirect anticoagulants for 6 months. under the control of the INR. Conclusion: The first experience of multicomponent plastic MV with strengthening of the fibrous ring with a vascular prosthesis shows the possibility of restoring the locking function and competence of the stored native valve without using the support rings.